Fisher information in generalized progressive hybrid-censored data. Issue 5 (3rd September 2018) - Sen, Tanmay; Pradhan, Biswabrata; Tripathi, Yogesh Mani; Bhattacharya, Ritwik
ABSTRACT: This article provides a simple expression of the Fisher information matrix about the unknown parameter(s) of the underlying lifetime model under the generalized progressive hybrid censoring scheme. The expressions of the expected number of failures and the expected duration of life test are also derived. Exponential and Weibull lifetime models are considered for numerical illustrations. Finally, Fisher information-based optimal schemes are discussed for the Weibull lifetime model.